Hubungan Job Crafting Terhadap Keterikatan Kerja Melalui Kepuasan Kerja - Rania Rahardini (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2020)
This study aims to determine the relationship of job crafting, work engagement and job satisfaction. This literature study is based on 20 empirical studies from national and international journals. Data is collected using a search engine. The results showed that job crafting had a positive relationship with work engagement and job satisfaction. This shows that the higher the job crafting done by the employee, the higher the work engagement. Job crafting has an important role to the level of job satisfaction of employees, because by doing crafting will make it easier for employees to complete their work. if, the higher the job crafting and employees' sense of engagement in the work, it will give employees a sense of satisfaction in completing work. Through job satisfaction, employees will tend to do crafting in their work that can simplify and improve their ability to work so as to increase work engagement with employees.